Izvajanje samoevalvacije z vidika profesionalne in zakonodajne odgovornosti šol za kakovost - Pevec, Marija (Revija za elementarno izobraževanje, 2013)
Self-Evaluation and Professional and Legal Responsibility of Schools Regarding Quality. The purpose of this paper was to outline the findings of a research study on professional and legal responsibility with regard to the quality of vocational education. We were interested in the elements of a systematic approach to quality, keeping in mind written development plans, their monitoring, and the efficiency of incorporating improvements into school practice. The methods chosen for the said research study were a combination of document research (public reports on school quality) and semi-structured interviews with head teachers. The concept of the research was based on theoretical and practical discoveries of professionals who were deeply involved with the process of self-evaluation in Slovenia and across Europe. The research showed that there were significant differences in the way quality was perceived by the selected schools, and that there was a non-uniform approach to self-evaluation.
Keywords: self-evaluation; quality; vocational education and training; head teacher